2022
DOI: 10.1021/acschemneuro.2c00556
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Dynamic Binding Behavior of PMX53 Cooperating with Allosteric Antagonist NDT9513727 to C5a Anaphylatoxin Chemotactic Receptor 1 through Gaussian Accelerated Molecular Dynamics and Free-Energy Perturbation Simulations

Abstract: C5a anaphylatoxin chemotactic receptor 1 (C5aR1) is an important target in anti-inflammatory therapeutics. The cyclic peptide antagonist PMX53 binds to the orthosteric site located in the extracellular vestibule of C5aR1, and the non-peptide antagonist NDT9513727 binds to the allosteric site formed by the middle region of TM3 (trans-membrane helix), TM4, and TM5. We catch a sight of the variational binding mode of PMX53 during the Gaussian accelerated molecular dynamic (GaMD) simulations. In the binary complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
4
4
0
Order By: Relevance
“…They reduced fluctuations of the intracellular domains of TM3, TM4, and TM5 ( Figure 2C-2E ), as well as ICL2 in β 2 AR ( Figure 2C ). This was consistent with recent finding that the NDT9513727 NAM stabilized TM5 through the hydrophobic stacking between TM4 and TM5 72 . Binding of NNC0640 to GLP1R and MK-0893 to GLR stabilized the lipid-facing pocket on the intracellular domains of TM7 and TM6, respectively ( Figure 2H, 2J and Supplementary Figure 4H, 4J ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…They reduced fluctuations of the intracellular domains of TM3, TM4, and TM5 ( Figure 2C-2E ), as well as ICL2 in β 2 AR ( Figure 2C ). This was consistent with recent finding that the NDT9513727 NAM stabilized TM5 through the hydrophobic stacking between TM4 and TM5 72 . Binding of NNC0640 to GLP1R and MK-0893 to GLR stabilized the lipid-facing pocket on the intracellular domains of TM7 and TM6, respectively ( Figure 2H, 2J and Supplementary Figure 4H, 4J ).…”
Section: Resultssupporting
confidence: 93%
“…Avacopan-binding to the C5AR1 confined the TM4 and TM5 extracellular domains from two conformational states to only state “S1”, where the TM4 and TM5 extracellular ends adopted the more closed conformation to stabilize NAM binding ( Figures 4E and 2E ). The hydrophobic stacking found between TM4 and TM5 extracellular ends was again in good agreement with previous finding by Xiaoli et al 72 . Binding of MK-0893 to the GLR confined the conformational space from three states (“S1”-S3”) to only state “S1”, in which the middle of TM5 and TM6 as well as TM6 and TM7 extracellular ends adopted the more closed conformations ( Figure 4J ).…”
Section: Resultssupporting
confidence: 92%
“…2C). This was consistent with recent nding that the NDT9513727 NAM stabilized TM5 through the hydrophobic stacking between TM4 and TM5 72 . Binding of NNC0640 to GLP1R and MK-0893 to GLR stabilized the lipid-facing pocket on the intracellular domains of TM7 and TM6, respectively (Fig.…”
Section: Gamd Simulations On Effects Of Allosteric Modulator Binding ...supporting
confidence: 93%
“…4E and 2E). The hydrophobic stacking found between TM4 and TM5 extracellular ends was again in good agreement with previous nding by Xiaoli et al 72 . Binding of MK-0893 to the GLR con ned the conformational space from three states ("S1"-S3") to only state "S1", in which the middle of TM5 and TM6 as well as TM6 and TM7 extracellular ends adopted the more closed conformations (Fig.…”
Section: Free Energy Pro Ling Of Important Residue Contacts In Gpcr A...supporting
confidence: 92%
“…FEP calculations not only allow for pose validation but can also provide mechanistic insight into conditional binding events. Xiaoli et al 26 reported FEP calculations for the cyclic peptide antagonist PMX53 binding to C5a anaphylatoxin chemotactic receptor 1 (C5aR1). Depending on whether the allosteric nonpeptide antagonist NTD9513727 was bound to C5aR1, binding of PMX53 to the binary or the ternary complex was favored by FEP providing energetic insights to the allosteric mechanism of NTD9513727.…”
Section: ■ Binding Pose Validationmentioning
confidence: 99%